Myelin oligodendrocyte glycoprotein antibody-associated cerebral cortical encephalitis: a case report highlighting diagnostic challenges and therapeutic implications - Liu, MengChan; Li, DaWei (Frontiers in Immunology, 2025)
Myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease (MOGAD) encompasses a spectrum of inflammatory demyelinating disorders of the central nervous system (CNS). Recognized clinical phenotypes include optic neuritis (ON), transverse myelitis (TM), acute disseminated encephalomyelitis (ADEM), brainstem encephalitis, aseptic meningitis, cortical encephalitis, demyelinating pseudotumor, and cranial nerve involvement. MOG antibody-associated cerebral cortical encephalitis (MOG-CCE) represents a rare but clinically significant subtype, often misdiagnosed due to heterogeneous clinical and neuroimaging features overlapping with other CNS disorders. We present a case of 36-year-old man with new-onset acute seizures and persistent headache. Initial brain magnetic resonance imaging (MRI) revealed no obvious signal abnormalities; however, subtle cortical swelling with sulcal effacement was identified in the left frontoparietal region, suggestive of focal cortical inflammation. Diagnostic workup revealed elevated MOG-IgG antibody titers in both serum and cerebrospinal fluid (CSF) using live cell-based assay. The patient demonstrated remarkable clinical response to combination immunotherapy with intravenous methylprednisolone and immunoglobulin. This case highlights the inclusion of MOG-CCE in the differential diagnosis of unexplained seizures and headaches accompanied by cortical swelling on neuroimaging, even in the absence of overt demyelinating lesions, and further underscores the critical role of early MOG-IgG testing and prompt immunotherapy to mitigate disease progression and improve neurological outcomes.